Influence of the Farm Harvest Prices on Acreage and Income From Sugarcane Crop in Haryana State of India - RANI USHA; RATHEE SUSHEELA; GODARA ABHEY; SIWACH MANOJ KUMAR (Zagadnienia Ekonomiki Rolnej)
The present study was carried out to examine the impact of farm harvest prices on the income of the farmers from sugarcane crop in Haryana, India. It also addresses the critical issue of acreage response to prices in the agricultural sector.